Kulturowoorganizacyjny kontekst kapitału intelektualnego : Studium Regionalnej Dyrekcji Lasów Państwowych w Poznaniu - Stańda, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The management of intellectual capital has been regarded for a long time by both theoretical and practical approaches as a modern instrument in managing a company. It has been considered as a basis for a pro-active creation of the future of an enterprise. Therefore, this approach assumes a radical re-orientation in term of planning and acting of the managers of a given organization. Consequently, the decision on the identification of the factors indicating the level of intellectual capital in the Regional Management of the National Forests in Poznan can be considered as a perfect example of the discussed approach. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 429-437